1980
DOI: 10.1002/j.1879-3479.1980.tb00283.x
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Smoking on Uteroplacental Blood Flow in Normotensive and Hypertensive Pregnancy

Abstract: The acute effect of smoking on uteroplacental blood flow was studied by the 133Xe method in 12 normotensive and 11 hypertensive pregnant women at term. A standard cigarette caused an acute decrease in intervillous blood flow in the normotensives but normalized within 15 minutes. In the other group, smoking produced a progressive increase in this flow, whose basal presmoking value lower in the hypertensive women. The myometrial blood flow was equal in both groups before smoking but significantly higher in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Our study also showed that 50% of the subjects" SBF dropped during smoking; the other 50%'s SBF remained relatively unchanged. Heart rate and BP also increased significantly with smoking, thus confirming findings of others (Coffman & Javett 1963, Trap-Jenson et al 1979. Lehtovirta & Forss 1980.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study also showed that 50% of the subjects" SBF dropped during smoking; the other 50%'s SBF remained relatively unchanged. Heart rate and BP also increased significantly with smoking, thus confirming findings of others (Coffman & Javett 1963, Trap-Jenson et al 1979. Lehtovirta & Forss 1980.…”
Section: Discussionsupporting
confidence: 86%
“…Smoking increases blood flow to skeletal muscle (Coffman & Javett 1963), intestines, and uterus (Lehtovirta & Forss 1980), but it decreases flow to forearm skin (Waeber et al 1984) and hands (Shepherd 1951, Freund & Ward I960, Drettner 1965. Sarin et al 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, it was fo und that ci ga ret te smo king dec re a sed the in ter vil lo us blo od trans fer acu tely which tur ned to nor mal 15 mi nu tes af ter stopping smo king. 24 In our study, when the fin dings of smo ker mot hers we re com pa red to ne ver smo ker mot hers, the per cen ta ge of pre ec lamp si a was hig her in the smokers. Ho we ver, this re sult was not sta tis ti cally sig ni fi cant.…”
Section: Referencesmentioning
confidence: 59%
“…In human pregnancies where there are adverse intra‐uterine conditions, such as an altered placental blood flow or infection, fetal growth can be compromised, leading to detrimental effects on brain development. Adverse conditions that can result in intra‐uterine growth restriction (IUGR) include maternal smoking, 1 substance abuse, 2,3 hypertension 4 and damage to, or abnormalities of, the placenta (for a review, see Robinson and Owen 5 ). Inadequate blood supply to the fetus via the placenta results in the restricted transfer of critical substrates, in particular oxygen, glucose, lactate and amino acids.…”
Section: Effects Of An Adverse Intra‐uterine Environmentmentioning
confidence: 99%